Institutions, management practices and challenges of small-scale irrigation systems in Ethiopia: a case study of two modern smallholders irrigation systems in western Oromia, Ethiopia - Dejene, S.; Teshome, W.; Makombe, Godswill; Awulachew, Seleshi Bekele; Prasad, Krishna Chandra (2008)
This paper examines the institutional arrangements that facilitate irrigation management and the present state of irrigation management and establishes where problems have occurred in the operation of Gibe-Lemu and Gambela-Terre Small-scale irrigation systems. The study employed the case study approach to tackle the research. Key informant and expert interview, desk review of different documents produced about the projects, group discussion, direct observation and structured interview schedule were used to collect data. The study proved the proposition that the government has uncritically supported the irrigation systems. Enabling legal system of land and water rights, strong woreda level state irrigation agency, support services (irrigation extension) and wellestablished water users associations through which purposes of irrigation are achieved were not adequately planned and put in place. These shortcomings undermined irrigation management, ultimately risked feasibility and sustainability of irrigated agriculture. Findings revealed poor record of accomplishment, in spite of the difference between the two systems, in managing water distribution in terms of the three most important performance indicators: adequacy, reliability and equity in water distribution. Water related conflicts are rampant but not settled yet. In addition, results indicated that irrigation had positively impacted irrigators? livelihoods in terms of diversification and intensification of crop production, household income, housing and employment generation and this social effect of irrigation was significantly different between irrigation systems (due to difference in the institutional and socioeconomic context of the two irrigation systems) and locations within irrigation systems. Nonetheless, many irrigators did not maintain these positive changes for long. The constraints were scarcity and unreliability of water and management and socioeconomic problems. These, in turn, were mediated by lack of: a) clearly defined and well enforced institutions of land and water rights; b) technical problems in design and construction; c) inadequate institutional capacity of the local state irrigation agency to coordinate and support decentralized management of irrigation; d) policy related problems; e) inadequate organization of users for self management; and f) problematic social relation of power among water users. Finally, the paper draws a number of conclusions, using the theoretical notions like context, social requirement for use, social effects and social construction, about policy options and requirements in the readjustment of the surveyed irrigation systems and in the design of irrigation projects of these types.